The Dark Side of the Mushroom Spring Microbial Mat: Life in the Shadow of Chlorophototrophs. I. Microbial Diversity Based on 16S rRNA Gene Amplicons and Metagenomic Sequencing - Thiel, Vera; Wood, Jason M.; Olsen, Millie T.; Tank, Marcus; Klatt, Christian G.; Ward, David M.; Bryant, Donald A. (Frontiers in Microbiology, 2016)
Microbial-mat communities in the effluent channels of Octopus and Mushroom Springs within the Lower Geyser Basin at Yellowstone National Park have been studied for nearly 50 years. The emphasis has mostly focused on the chlorophototrophic bacterial organisms of the phyla Cyanobacteria and Chloroflexi. In contrast, the diversity and metabolic functions of the heterotrophic community in the microoxic/anoxic region of the mat are not well understood. In this study we analyzed the orange-colored undermat of the microbial community of Mushroom Spring using metagenomic and rRNA-amplicon (iTag) analyses. Our analyses disclosed a highly diverse community exhibiting a high degree of unevenness, strongly dominated by a single taxon, the filamentous anoxygenic phototroph, Roseiflexus spp. The second most abundant organisms belonged to the Thermotogae, which have been hypothesized to be a major source of H2 from fermentation that could enable photomixotrophic metabolism by Chloroflexus and Roseiflexus spp. Other abundant organisms include two members of the Armatimonadetes (OP10); Thermocrinis sp.; and phototrophic and heterotrophic members of the Chloroflexi. Further, an Atribacteria (OP9/JS1) member; a sulfate-reducing Thermodesulfovibrio sp.; a Planctomycetes member; a member of the EM3 group tentatively affiliated with the Thermotogae, as well as a putative member of the Arminicenantes (OP8) represented ≥1% of the reads. Archaea were not abundant in the iTag analysis, and no metagenomic bin representing an archaeon was identified. A high microdiversity of 16S rRNA gene sequences was identified for the dominant taxon, Roseiflexus spp. Previous studies demonstrated that highly similar Synechococcus variants in the upper layer of the mats represent ecological species populations with specific ecological adaptations. This study suggests that similar putative ecotypes specifically adapted to different niches occur within the undermat community, particularly for Roseiflexus spp.